Comparative SEM–EDS Characterization of Marine Sand from Multiple Coastal Regions of Central Indonesia for Engineering Applications - Adnan; Tumpu, Miswar; Muhammadiyah, Muhammad Jabir; Yunianta, Andung; Lee, Hoong-Pin (Engineering, Technology & Applied Science Research, 2026)
Marine sand is an alternative construction material due to the growing demand for natural aggregates and the depletion of terrestrial resources. Its use also aligns with the Sustainable Development Goals (SDGs), particularly SDG 9, SDG 11, and SDG 12. This study examines the mineralogical and elemental characteristics of marine sand collected from several coastal regions in central Indonesia, including South Sulawesi (Balusu Barru, Bojo Barru, Pangkep, Pare-Pare, Pinrang, and Selayar) and East Kalimantan (Muara Badak), using Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (SEM–EDS). The results indicate regional variations in particle morphology, surface texture, and elemental composition, reflecting differences in geological setting and coastal sediment processes. Several samples exhibit silica-dominated characteristics, while others show higher contents of calcium (Ca)-, magnesium (Mg)-, and iron (Fe)-bearing phases, suggesting varying levels of suitability for engineering applications. SEM–EDS analysis reveals silicon (Si) contents ranging from approximately 2.9 to 12.8 wt.% and Ca contents between 0.0 and 18.5 wt.%. The novelty of this study lies in its comparative regional assessment, demonstrating that marine sand should not be treated as a homogeneous material across different coastal environments. From an engineering perspective, the findings provide valuable insights for material selection in concrete, mortar, and geotechnical applications, particularly for coastal infrastructure development, while emphasizing the importance of site-specific characterization to support sustainable material utilization and environmentally responsible construction practices.